Peningkatan Kemampuan Terapi Spiritual Emotional Freedom Technique (SEFT) untuk Perokok pada Kelompok Ibu PKK - Rahim, Fitri Kurnia; Hamdan , Hamdan; Aini, Khusnul; Muzdhalifah, Nazwa Aulya; Ananda, Revansa Fitria; Maulana, Efan Samsiatul Fazri (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2026)
Background: Cigarette smoke affects both active and passive smokers. Smoking is a risk factor for non-communicable diseases, one of which is hypertension, which can lead to other diseases. Therefore, efforts and strategies are needed to reduce smoking behavior in the community. Spiritual Emotional Freedom Technique (SEFT) therapy is a relatively affordable and efficient non-pharmacological complementary therapy for smoking cessation. Empowering the Family Empowerment and Welfare (PKK) Mothers' Group is one way to strengthen the community's health, especially through promotive and preventive measures to reduce smoking. The purpose of this community service is to increase the PKK Mothers' Group's knowledge and skills in addressing smoking behavior by providing SEFT therapy in the Pasiragung Village area, Hantara District. The partners of the community service activity are the PKK Mothers' Group, comprising 35 people. Method: The method used is Training and Mentoring in conducting SEFT Therapy. The stages of the activity are initial screening, counseling, and training in SEFT Therapy, mentoring SEFT Therapy interventions for smokers, and the final stage is evaluation. Results: Showed that PKK mothers experienced increased knowledge and improved their ability to perform SEFT therapy on smokers. Eighty-eight percent of PKK mothers who demonstrated SEFT therapy skills were categorized as Good. Meanwhile, 2 percent of PKK mothers demonstrated very good SEFT therapy skills. Conclusion: The sustainability of this program is achieved by integrating the SEFT Therapy program into the routine activity agenda, the PKK work program, or the village integrated health post.